Estudo de ações sustentáveis para o exercício da construção civil com base em análise dos impactos ambientais gerados - Araujo, Juliano Sousa de [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The Civil construction is an industry of paramount importance for the Brazilianeconomy,employing thousands of workers. However, its activity generates impacts of vast proportions,starting with the following environmental aspects: from the extraction of materials andtheirmisuse during a work to the maximum amount of waste generated in renovationsanddemolitions, which ends up being dumped incorrectly in places and conditions inappropriate.In this sense, through a bibliographic survey, this work will focus on identifyingtheenvironmental problems generated in the construction stage, and the inappropriate destinationof the waste. As well as, possible aggravating factors in the Brazilian scenario will alsobeanalyzed: unprepared labor; an omitted public sector that does not control constructionwaste;and the lack of proper management of the works. Finally, new construction techniques will bepointed out, present in recognized bibliographies, which go against combating the generationof the identified environmental impacts, which bring greater industrializationtotheconstruction. In addition to the construction techniques, an economic and environmentalcomparison will be performed between two construction systems: Conventional SystemofConstruction and Light Steel Frame. This comparison contributes to verify if, despitetheenvironmental gains, there is applicability of costs of other construction methodswhencompared to the Conventional System. In conclusion, after the research it was possibletoidentify several strategies that combat the environmental impact, through actions that applyplanning, adequate management and innovative techniques, it is possible to reducethegeneration of waste in addition to the consumption of materials. And, when combinedwithother mitigating measures that aim to raise awareness and instruct the population andworkers,they can considerably reduce their negative consequences, thus bringing greater sustainability,and making civil construction “greener”.

A construção civil é uma indústria de suma importância para a economia brasileira, empregando milhares de trabalhadores. Porém, sua atividade gera impactos de vastas proporções, a começar pelos ambientais desde a extração dos materiais e o seu mau uso durante a obra, até a grande quantidade de resíduos gerados em reformas e demolições, que terminam por ser despejados incorretamente em locais e condições inapropriadas. Neste sentido, por meio de um levantamento bibliográfico, este trabalho focará em identificar os problemas ambientais gerados na etapa de construção e na destinação inadequada dos resíduos. Serão analisados também possíveis agravantes do cenário brasileiro: a mão de obra despreparada; um setor público omisso que não controla os resíduos de construção; e a falta de um gerenciamento adequado das obras. Por fim, serão apontadas novas técnicas da construção, presentes em bibliografias reconhecidas, que vão de encontro ao combate à geração dos impactos ambientais identificados, e que trazem maior industrialização para a construção. Além das técnicas de construção, será executado um comparativo econômico e ambiental entre dois sistemas construtivos: Alvenaria Convencional e Light Steel Frame. O que contribui para verificar se, apesar dos ganhos ambientais, há aplicabilidade de custos de outros métodos construtivos quando comparados ao Sistema Convencional. Finalmente, após a pesquisa foi possível identificar diversas estratégias que combatem o impacto ambiental por meio de ações que incluem planejamento, uma gestão adequada e técnicas inovadoras, sendo possível reduzir a geração de resíduos, além do consumo de materiais. E, quando estas ações são aliadas a outras medidas mitigadoras que visem conscientizar e instruir a população e os trabalhadores, possibilita-se diminuir consideravelmente suas consequências negativas, trazendo maior sustentabilidade, e tornando a construção civil mais “verde”.
Study of sustainable actions for the exercise of civil construction based on analysis of environmental impacts generated
Keywords: Civil construction industry - environmental aspects; Waste management; Sustainable construction; Indústria de construção civil – aspectos ambientais; Gerenciamento de resíduos; Construção sustentável